Oblique propagation of arbitrary amplitude ion acoustic solitary waves in anisotropic electron positron ion plasma - Almas,; Ata-ur-Rahman,; Khalid, Muhammad; Eldin, Sayed M. (Frontiers in Physics, 2023)
The oblique propagation of arbitrary ion acoustic solitary waves (IASWs) in magnetized electron, positron, ion plasmas is investigated by employing Sagdeev pseudopotential approach. Ions are assumed to be adiabatic having anisotropic thermal pressure. Electrons and positrons are considered to be isothermal, following Maxwellian distribution. In terms of electrostatic potential, Sagdeev potential function is obtained and analyzed numerically in the context of relevant plasma configuration parameters. The existence region of solitary pulses is defined accurately. It is investigated how several plasma configuration parameters, such as the positron concentration, electron to positron temperature ratio, obliqueness, parallel, and perpendicular ion pressure, affect the properties of solitary waves.